Investigation of Optimal Power Flow with TCSC using Differential Evolution - Bhardwaj, Abhishek (My University, 2013)
Optimal Power Flow (OPF) plays an important role in power system operation and planning. The OPF mainly aims to optimize the selected objective function such as fuel cost, active power loss via optimal adjustment of power system control variables, while at the same time satisfying various equality and inequality constraints. In recent years, FACTS devices have opened a new world in power system control. They have made the power systems operation more flexible and secure. In the power flow studies, circuit impedance, voltage magnitude and phase angle are important parameters. In this dissertation work, the TCSCs are incorporated using reactance model at fixed locations and power flow studies are carried out using Newton Raphson method. Differential evolution strategy is used to optimize the parameters like bus voltages, angles, generation cost and the reactance values of TCSC. The proposed strategy which is best suited for solving non-convex optimization problems, has been implemented on IEEE 14 bus system and it shows better results when compared with conventional iterative procedure.
ME, EIED
Keywords: optimal power flow,differential evolution; TCSC, Looad flow